Robotic Surgery of Colon and Rectum - Ceccarelli, Graziano; Coratti, Andrea (Updates in Surgery, 2024)
This is an open access book. Colorectal surgery is one of the most performed procedures in dedicated colorectal and general surgery units worldwide. In the last two decades, the minimally invasive laparoscopic approach has become very popular worldwide, attracting great interest among patients (lower risk of infection, less pain, and faster recovery) and demonstrating excellent oncological results. Technology is improving rapidly, offering revolutionary innovations, particularly with the advent of robotic surgery, which offers important advantages over laparoscopy for both surgeons and patients: improved ergonomics, wristed instruments, and a better vision. These advantages may be particularly useful for more complex and challenging situations (complete mesocolic excision, low rectal cancer, one-stage treatment of colorectal and liver metastases, etc.), translating into potential improved surgical and oncological results. Although several books have been published on the subject, the great interest in robotic surgery makes it mandatory, in our opinion, to have a general update in view of the latest technical innovations and the results of the most relevant and recent literature. The book is divided into chapters dealing with the different colorectal segments with their robotic surgical operations and specific technical variants. The new frontiers of benign and emergency colorectal diseases are also considered, as well as the new robotic platforms recently introduced in the healthcare market. Some of them, such as the da Vinci SP single port device, may represent a revolutionary approach for this surgery. Training and cost aspects were also considered.